The Relationship between Individual Workload Perception and Individualized Care Perceptions of Nurses - Kevser Pamuk; Pakize Özyürek (Association of Nurse Managers, 2022)
Aim: The purpose of the study was to examine the relationship between nurses' perceptions of individual workload and perceptions of individualized care. Method: The study was a descriptive cross-sectional and conducted with 424 nurses. 'Nurse Information Form', 'The Individual Workload Perception Scale (IWPS-R)', and 'the Individualized Care Scale: Nurse A version (ICS Nurse-A)' were used as data tools. Results: The nurse's IWPS-R score was 3.50+-0.67, and the ICS- Nurse A was 3.48+-0.82. The factor that contributed most to nurses' positive perceptions of their workload was 'peer support' and the factor with the least contribution was 'manager support'. 'Clinical situation' was the subscale with the highest mean score (3.70+-0.87), and 'personal life situation' was the subscale with the lowest score in ICS-Nurse A (2.99+-0.98). The nurses' perceptions of their workload and individualized nursing care were at moderately positive levels, and there was a significant correlation between them. The one unit increase in the individual workload' perception of nurses would lead to a 0.447 unit increase in their perception of individualized care. Conclusions: Nurses' perceptions of individual workload were rated as moderately positive. There was a statistically significant relationship between perceived individual workload and individual nursing care.